What Do We Know about Poverty in India in 2017/18? - Edochie, Ifeanyi Nzegwu (World Bank, Washington, DC, 2022)
This paper nowcasts poverty in India, one of the countries with the largest population below the international poverty line of $1.90 per person per day. Because the latest official household survey dates back to 2011/12, there is considerable uncertainty about recent poverty trends in the country. Applying a pass-through and survey-to-survey methodology, extreme poverty (at the $1.90 poverty line) for India in 2017 is estimated at 10.4 percent with a confidence interval of [8.1, 11.3]. The urban and rural poverty rates are estimated at 7.2 and 12.0 percent, respectively. Across a wide range of publicly available data sources, the paper finds no evidence of an increase in poverty between 2011/12 and 2017/18.